Efficacy and safety of two different adjuvant chemotherapy regimens in combination with concurrent chemoradiotherapy in treating patients with advanced nasopharyngeal carcinoma: A protocol for randomized controlled trial. Issue 21 (28th May 2021) - Zhang, Lu-Lu; Cui, Jun; Tan, Hong-Fei; Xiao, Zheng; Pan, Li-Xia
Abstract: Background: Concurrent chemoradiotherapy is widely utilised as a standardized primary method of treatment for patients with advanced nasopharyngeal carcinoma (NPC). However, the combination of concurrent chemoradiotherapy and adjuvant chemotherapy for treating NPC patients remain unclear. Therefore, this study attempts to elucidate the efficiency and safety of concurrent chemoradiotherapy combined with adjuvant chemotherapy (gemcitabine plus cisplatin versus 5-fluorouracil plus cisplatin) for treating patients with NPC. Materials and Methods: This study is a randomized, multicentral, open-labelled trial to assess the clinical efficiency and safety of using concurrent chemoradiotherapy combined with adjuvant chemotherapy as a therapeutic measure for advanced NPC patients. A total of 50 patients will be randomly assigned into 2 groups, namely treatment-group-one and treatment-group-two. Eligible patients will be administered with concurrent chemoradiotherapy and subsequentially with adjuvant chemotherapy (gemcitabine plus cisplatin or 5-fluorouracil plus cisplatin). Moreover, the primary endpoint is a comparison of progression-free survival between concurrent chemoradiotherapy and subsequentially adjuvant gemcitabine and cisplatin and chemoradiotherapy, which is proceeded by adjuvant 5-fluorouracil and cisplatin in advanced NPC patients. Overall survival, overall response rate, incidence of acute and late toxicity, and adverse events are the minor endpoints. Statistical analyses will be performed with SPSS 25.0 software. Discussion: The current research evaluates the clinical efficiency and safety of utilising concurrent chemoradiotherapy combined with adjuvant chemotherapy as a therapeutic strategy to treat advanced NPC patients. The work done in this study will provide a clinical basis for concurrent chemoradiotherapy in combination with adjuvant chemotherapy for treating advanced NPC. Trial registration: DOI 10.17605/OSF.IO/5UPVM.